ANALISIS FAKTOR-FAKTOR YANG MENENTUKAN KINERJA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2016-2021 - Marsana, Marsana; Karyawati, Danik; Sunarya, Sunarya (UNPERBA, 2022)
This research aims to investigate the influence of the Current Ratio (CR) on the performance of manufacturing companies listed on the Indonesia Stock Exchange (IDX). The study was conducted on manufacturing companies listed on the IDX for the period 2016-2021. The data used in this research were obtained from the Indonesia Stock Exchange office, located at Jalan P. Mangkubumi Number 111, Cokrodiningratan, Jetis, Yogyakarta City, along with supporting websites such as www.idx.co.id and finance.yahoo.com. The research was conducted from January 2022 until completion. The analysis results indicate that the CR variable has a probability rounded to 0.05 and a regression coefficient of 0.007062. The CR variable influences the 5% significance level, with a probability value of CR being 0.05, which is equal to 0.05. This indicates that the CR variable individually has a significant influence on the performance of manufacturing companies listed on the IDX. The regression coefficient value indicates that CR has a positive effect on company performance. This means that an increase of 1% in CR will lead to a 0.007% increase in the performance of manufacturing companies listed on the IDX.